2013
DOI: 10.1097/inf.0b013e31828afb2a
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Changes in Kenyan HIV-1–infected Infants Initiating Highly Active Antiretroviral Therapy by 1 Year of Age

Abstract: Background Early highly active antiretroviral therapy (HAART) is recommended for HIV-1 infected infants. There are limited data on lipid changes during infant HAART. Methods Non-fasting total (TC), low density lipoprotein (LDL), and high density lipoprotein (HDL) cholesterol, and triglycerides (TG) were measured at 0, 6 and 12 months. Correlates of lipid levels and changes post-HAART were assessed using linear regression. Results Among 115 infants, pre-HAART median age was 3.8 months, CD4% was 19%, and wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…This study found increased rates of elevated TC in a South African adult population on ART and found that, consistent with previous reports , TDF had a favourable impact on TC compared with other NRTIs. A strength of our study is that close to 95% of our patients were initiated on EFV, eliminating the possibility that the difference in TC levels associated with the NRTIs used (TDF vs .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study found increased rates of elevated TC in a South African adult population on ART and found that, consistent with previous reports , TDF had a favourable impact on TC compared with other NRTIs. A strength of our study is that close to 95% of our patients were initiated on EFV, eliminating the possibility that the difference in TC levels associated with the NRTIs used (TDF vs .…”
Section: Discussionsupporting
confidence: 92%
“…The impact of ART on lipid profiles varies depending on the ART regimen used , further complicated by the fact that HIV alone has been shown to affect lipid profiles . Briefly, the non‐nucleoside reverse transcriptase inhibitors (NNRTIs) efavirenz (EFV) and nevirapine (NVP) as well as the nucleoside reverse transcriptase inhibitors (NRTIs) stavudine (d4T) and zidovudine (ZDV) have all been shown to increase total cholesterol (TC), low‐density lipoprotein cholesterol (LDL‐c), high‐density lipoprotein cholesterol (HDL‐c) and triglycerides . Similarly, most protease inhibitors (PIs) are also thought to increase TC and LDL‐c, but have been shown to decrease HDL‐c .…”
Section: Introductionmentioning
confidence: 99%
“…6 Dyslipidemia has been observed even in the absence of any HIV treatment, 5,6 but usually worsens with antiretroviral drugs (ART), 5,7,8 especially if protease inhibitors (PIs) are used. 9,10 To the best of our knowledge, there is no published study reporting on the prevalence of dyslipidemia and its association with PI among HIV-infected children in Central America.…”
mentioning
confidence: 99%
“…HIV infection has become a chronic disease in children because of prolonged survival resulting from ART and also because of its adverse effects [19,56]. Because of the deleterious effects of metabolic changes, prevention of morbidity, in the short term and the long term, is important to avoid further complications in adulthood [16].…”
Section: Metabolic Abnormalitiesmentioning
confidence: 99%
“…These metabolic disorders may result in increased cardiovascular diseases in the medium and long terms as well as reduced bone mineral density [13][14][15][16][17][18][19]. These metabolic disorders may result in increased cardiovascular diseases in the medium and long terms as well as reduced bone mineral density [13][14][15][16][17][18][19].…”
mentioning
confidence: 99%